Intraseasonal Abyssal Current Variability of Bottom-Trapped Topographic Rossby Waves in the Southwestern East Sea (Japan Sea) - Shin, JiYun; Noh, Suyun; Nam, SungHyun (Frontiers in Marine Science, 2020)
Examining the deep-water exchange through the Ulleung Interplain Gap (UIG) between the Ulleung Basin (UB) and the Japan Basin in the East Sea (Sea of Japan) is critical for understanding the vigorous circulation and material cycles of the sea. The exchange features an asymmetric flow structure across the UIG: a broad and weak inflow (into the UB) in the western UIG, and a narrow and strong outflow (out of the UB) in the eastern UIG, with the latter closely associated with the Dokdo Abyssal Current (DAC), a long-term mean, strong abyssal current near Dokdo. In this study, the linear theory of bottom-trapped topographic Rossby waves (TRWs) is applied to explain the previously unexplored longer intraseasonal band (30–50 days) DAC variability by analyzing multi-year moored current-meter observations and HYCOM reanalysis data, as they are significantly correlated in the period band (though not at the shorter intraseasonal band of 5–25 day explored previously). Bottom-intensified DAC variability is characterized by TRW parameters with a vertical trapping scale of 1100–2100 m, a horizontal wavelength of 49–111 km, a propagating speed of 1.3–3.0 km day–1, and a propagating direction aligned with isobaths within a 2°–23° range (shallower water on the right). The departure angle between the energy-propagating direction of the waves and the isobath direction is estimated from the spectra of the along- and cross-slope abyssal currents and from the TRW theoretical dispersion relation for a given buoyancy frequency and bottom slope. These values are then compared to examine the significance of the bottom-trapped TRW dynamics, yielding a small (<16°) difference. The results support the significance of bottom-trapped TRWs on the longer intraseasonal variability of abyssal currents near the steeply sloped eastern side of the UIG, and an asymmetric abyssal flow structure across the UIG in the southwestern East Sea.